Metagenomic sequencing, molecular characterization, and Bayesian phylogenetics of imported type 2 vaccine-derived poliovirus, Spain, 2021 - Fernandez-Garcia, Maria Dolores; Faye, Martin; Diez-Fuertes, Francisco; Moreno-Docón, Antonio; Chirlaque-López, Maria Dolores; Faye, Ousmane; Cabrerizo, Maria (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction: In 2021, a type 2 vaccine-derived poliovirus (VDPV2) was isolated from the stool of a patient with acute flaccid paralysis (AFP) admitted in Spain from Senegal. A virological investigation was conducted to characterize and trace the origin of the VDPV2. Methods: We used an unbiased metagenomic approach for the whole-genome sequencing of the VDPV2 from the stool (pre-treated with chloroform) and from the poliovirus-positive supernatant. Phylogenetic analyses and molecular epidemiological analyses relying on the Bayesian Markov Chain Monte Carlo methodology were used to determine the geographical origin and to estimate the date of the initiating dose of the oral poliovirus vaccine for the imported VDPV2. Results: We obtained a high percentage of viral reads per total reads mapping to the poliovirus genome (69.5% for pre-treated stool and 75.8% for isolate) with a great depth of sequencing coverage (5931 and 11581, respectively) and complete genome coverage (100%). The two key attenuating mutations in Sabin 2 strain had reverted (A481G in 5’UTR and Ile143Thr in VP1). In addition, the genome had a recombinant structure between type-2 poliovirus and an unidentified non-polio enterovirus-C (NPEV-C) strain with crossover point in the protease-2A genomic region. VP1 phylogenetic analysis revealed that this strain is closely related to VDPV2 strains circulating in Senegal in 2021. According to Bayesian phylogenetics the most recently common ancestor of the imported VDPV2 could date back 2.6 years (95% HPD: 1.7-3.7) in Senegal. We suggest for all VDPV2s circulating in 2020-21 in Senegal, Guinea, Gambia and Mauritania an ancestral origin in Senegal estimated around 2015. All 50 stool samples collected in Spain (n=25) and in Senegal (n=25) and four wastewater samples collected in Spain were poliovirus-negative. Discussion: By using a whole-genome sequencing protocol with unbiased metagenomics from the clinical sample and viral isolate with a high sequence coverage, efficiency and throughput, we confirmed the classification of the VDPV as a circulating type. The close genomic linkage with strains from Senegal was consistent with classification as imported. Given the scarce number of complete genome sequences for NPEV-C in public databases, this protocol could help to expand poliovirus and NPEV-C sequencing capacity worldwide.